Plasma serotonin in patients with chronic tension headaches. Issue 2 (February 1989) - Anthony, M; Lance, J W
Abstract : Previous reports have suggested that platelet level of serotonin in chronic tension headache (CTH) is lower than in normal control subjects, and that there is continuous activation of platelets both in migraine and in CTH. In this study we compared platelet serotonin concentration in 95 patients with CTH, 166 patients with migraine and 35 normal control subjects. Mean platelet serotonin (ng/10(9) platelets) was 310 for the CTH group, 384 during migraine headache, 474 for normal control subjects and 514 in headache-free migrainous patients. There was significant statistical difference of values between CTH patients and those of normal control subjects as well as headache-free migrainous patients, but not of those of migrainous patients during headache. It is suggested that CTH is a low serotonin syndrome, representing one end of the spectrum of idiopathic headache, the other end being represented by migraine.